Evaluating the clinical relevance of the enterotypes in the Estonian microbiome cohort - Aasmets, Oliver; Krigul, Kertu Liis; Org, Elin (Frontiers in Genetics, 2022)
Human gut microbiome is subject to high inter-individual and temporal variability, which complicates building microbiome-based applications, including applications that can be used to improve public health. Categorizing the microbiome profiles into a small number of distinct clusters, such as enterotyping, has been proposed as a solution that can ameliorate these shortcomings. However, the clinical relevance of the enterotypes is poorly characterized despite a few studies marking the potential for using the enterotypes for disease diagnostics and personalized nutrition. To gain a further understanding for the clinical relevance of the enterotypes, we used the Estonian Microbiome cohort dataset (n=2506) supplemented with diagnoses and drug usage information from electronic health records to assess the possibility for using enterotypes for diseases diagnostics, detecting disease subtypes and evaluating the susceptibility for developing a condition. In addition to the previously established 3-cluster enterotype model, we propose a 5-cluster community type model based on our data, which further separates the samples with extremely high Bacteroides and Prevotella abundances. Collectively, our systematic analysis including 231 phenotypic factors, 62 prevalent diseases and 33 incident diseases greatly expands the knowledge about the enterotype-specific characteristics, however, the evidence suggesting practical use of enterotypes in clinical practice remains scarce.